Cross adaptation and the laws of training level transfer - Razumov, A. N.; Pavlov, S. E.; Pavlov, A. S. (The Russian Journal of Physical Education and Sport, 2016)
Annotation. One of the scientific problems, which is considered by the scientists, who studied adaptive changes in an organism under the influence of different factors and interference of these changes on different functions of an organism is the problem of "cross adaptation". The significance of a person`s organism adaptation laws for sports science and practice is obvious. However, even nowadays we can see absolutely different opinions concerning the essence of adaptation process and its role in sports-pedagogical process. Research methods: scientific literature analysis and summarizing, experiment, observation, testing, the methods of mathematical statistics. Result. An absolute importance of adaptation laws for the theory and methodology of sport is underlined. One of the mentioned in the literature effects of adaptation is considered, which is the effect of "cross adaptation" in sport. "Advantages" and "disadvantages" of "cross adaptation" effects in sport are revealed. The conditions of general and specific physical training unity principle work are specified. An absolute interconnection of the notions "cross adaptation" and "training level transfer"inner contents in sport is revealed. The principles of "training level transfer" in sport are presented schematically. It is stated, that the training exercises of non-specific character during the effect of "training level transfer" realization from these exercises to the main competitive exercise have both positive and negative effects. The example of a negative "training level transfer" from one exercise to another, stated in the experiment with qualified hockey players, is presented. The hypothesis of "a resonance training level transfer" is mentioned, which is to explain stated in practice of training sportsmen positive effects of "training level transfer" from non-specific exercises to the main competitive exercise. The conditions are described, which help to use positive effects of "cross adaptation" in training sportsmen. The example is given of a positive "cross adaptation" effect realization in the experiment with young qualified hockey players. The importance of "cross adaptation" effect is underlined in the theory and practice of sport. Conclusion. Thus, "cross adaptation" effect plays a great role in a long-term training of sportsmen. The absence of knowledge concerning this effect and inability to use it in practice with sportsmen leads a trainer to inability to control the training process and demand sports realization of the potential from his sportsmen.